Estudo sobre o comportamento e a adaptação muscular em modelo de oclusão da carótida comum em gerbilos - Turi, Andriette Camilo (Universidade Federal de São Carlos, 2015)
Among the disorders resulting from cerebrovascular accident (CVA), the sensorimotor are the most prevalent and the most disabling, especially muscle weakness. Complex and unknown etiology, this weakness has been related to muscle disorders, such as atrophy. The common carotid artery occlusion model (ACC) in gerbils has been described as effective in inducing neuronal damage in the hippocampus and motor areas. However, no information is available about which muscle adaptation due to this model. To assess the effectiveness of an ischemic stroke induction model by unilateral CCA occlusion followed by reperfusion of the muscle changes over 7, 15 and 21 days in gerbils. To this end, the quantification of the cross-sectional area of muscle fibers and quantification of protein content Fbxo40, a modulator of muscle hypertrophy in paretic muscles (P) and not paretic (NP) were related to data obtained in open field test and Rota Rod. MATERIALS AND METHODS: Seventy adult male gerbils (Meriones unguiculatus), 2-3 months, underwent unilateral occlusion of the common carotid artery for 10 minutes, with suture, followed by reperfusion. The exploratory and motor behaviors were evaluated by open field tests and Rota Rod, respectively, the day before the injury and 6, 13 and 20 days after surgery. A sham group for the surgical procedure was performed. The animals were killed on the 7th, 14th or 21st day. Morphometric analysis (cross-sectional area of muscle fibers) of the tibialis anterior and soleus muscles were performed. The quantification of the protein content of the Fbxo40 atrophy enzyme was analyzed by Western blot and histological sections of the regions of the hippocampus, motor cortex and striatum were performed. Statistical data were subjected to homogeneity and normality tests. If detected that the data were parametric, the one-way ANOVA test was used. If there is a difference, the Tukey test was used to locate them. Nonparametric, the Kruskal-Wallis test followed by Mann-Whitney test was performed. A 5% significance level was considered. RESULTS: There was no difference in the number of crossings evaluated by field tests, as well as the residence time in the apparatus Rota Rod in the comparison between the experimental groups (p> 0.05). Protein expression of Fbxo40, muscle weight and cross-sectional area of muscle fibers of the tibialis anterior and soleus muscles of both legs pelvic did not differ between the experimental groups (p> 0.05). CONCLUSION: The induction stroke model in gerbils with 10 minutes of occlusion of the common carotid artery with reperfusion, was unable to produce functional or behavioral changes in gerbils muscle.
Keywords: Fisioterapia; Acidente vascular encefálico; Isquemia; Músculo esquelético; Stroke; Physiotherapy; Model of ischemia; Skeletal muscle; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL